Mental hygiene : essays on writers and writing - Robertson, Ray, 1966- (Insomniac Press, 2003)
One of today's best young novelists, Ray Robertson is also one of its ablest critics. Mental Hygiene is a collection of his most entertaining, insightful, controversial, and funniest reviews and essays written over the last five years. Believing that ''writers have a responsibility to help maintain the mental hygiene of their time, '' Robertson, following in the footsteps of Mordecai Richler and other novelist-critics such as Anthony Burgess, Kingsley and Martin Amis and John Updike, is at the front line of contemporary literary debate. Whether castigating the bland cabal he refers to as McCanl.